Obtención de ácido hialurónico mediante Streptococcus zooepidemicus empleando como fuente de sustrato residuos de la industria láctea. (2022)
The present degree project includes areas of innovation and technological development of Chemical Engineering, employing bioprocesses and kinetics of microbial growth, in order to define an efficient process for the production of hyaluronic acid by the bacterium Streptococcus zooepidemicus using whey as substrate.